A study on the attributes that contribute to the success of restaurants / Nur Adilah Saud - Saud, Nur Adilah (2002)
The research is conducted to study the attributes that contribute to the success of restaurants. There are several factors that influence the success of restaurants. Besides that, this study also determines the characteristics of the owners of restaurants that influence the successful of restaurant. In order to be successful there are also some problems need to be faced by the owners of restaurants. From this research the owners of restaurants can determine the problems that they faced. So, it will be easy for them to find the best way to solve it. This project paper consists of five chapters, which bring its own exploration to the topic being explored. Chapter one is a comprehensive discussion about the organization and background of the study. Chapter two is the literature review where the topics and matters concern is explain. Its explanation is related to the Subject studied. Chapter three is the research methodology. 30 questionnaires has been distributed randomly to the owner of restaurants in Batu Berendam, Malacca. The data were coded and analyzed using Statistical Package for Social Science (SPSS) 10.0 in order to get the findings in chapter four. Chapter five contains the conclusion and recommendations given by the researcher.